2016
DOI: 10.30843/nzpp.2016.69.5886
|View full text |Cite
|
Sign up to set email alerts
|

How many conidia are required for wound infection of apple plants by <i>Neonectria ditissima</i>

Abstract: A series of experiments using potted plants in a glasshouse detached laterals in the laboratory and trees in the fi eld were undertaken to study wound size and number of Neonectria ditissima conidia required to produce European canker infections on freshlymade branch wounds in the apple cultivars Royal Gala and Scilate Th e wound types were needle and pin injuries rasp wounds and pruning cuts Spore concentrations from 102 to 106 conidia/ml and two inoculation methods (droplet and mist) were used Disease expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 9 publications
(15 reference statements)
2
46
0
Order By: Relevance
“…Large wounds will be difficult to protect from N. ditissima with captan-based fungicides. The effect of wound size is in agreement with earlier work by Walter et al (2016) showing that the larger the wound, the more infection will occur and the shorter the incubation and latent periods (infection to symptom expression and infection to spore production, respectively). A shorter latent period was also observed for picking and rasp wounds than for leaf scars, with disease assessments completed earlier for the former.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Large wounds will be difficult to protect from N. ditissima with captan-based fungicides. The effect of wound size is in agreement with earlier work by Walter et al (2016) showing that the larger the wound, the more infection will occur and the shorter the incubation and latent periods (infection to symptom expression and infection to spore production, respectively). A shorter latent period was also observed for picking and rasp wounds than for leaf scars, with disease assessments completed earlier for the former.…”
Section: Figuresupporting
confidence: 91%
“…In each plot, 40 picking wounds on spurs (20 either side of the plot) and 20 one-year-old shoots for rasp wound inoculations (10 either side of the plot) were chosen from different trees at random. Two rasp wounds per one-year-old shoot were made as described by Walter et al (2016). Rasp wounds were included as additional wound controls.…”
Section: Picking and Rasp Wound Experimentsmentioning
confidence: 99%
“…In the Tasman district of New Zealand, both spore types are readily produced all year round in older lesions caused by wound infections in apple trees . Recent research has also shown that large wounds are more susceptible to infection Walter et al 2016). Spur lesions resulting from picking wound infections dominate in the Tasman apple-growing district followed by shoot lesions from leaf scar infections .…”
Section: Introductionmentioning
confidence: 99%
“…Buddy tape prevented infection of chip-buds with N. ditissima inoculum applied immediately after budding, as well as 1 month after budding when the tape had been exposed to the elements for a month. Walter et al (2016) showed that only 3 to 30 conidia were required to infect wounds of various sizes. In this study, approximately 12,000 conidia were sprayed towards each bud, which ensured that even if most of the inoculum missed the wound, the taped buds were still exposed to a very high (a) (b) Figure 2 Budded 'EMLA 9' apple rootstocks, 3 months after budding with 'Royal Gala' and inoculation with a conidial suspension (2×10 5 conidia /ml) of Neonectria ditissima.…”
Section: Discussionmentioning
confidence: 99%